Association between Plasmatic Ceramides Profile and AST/ALT Ratio: C14:0 Ceramide as Predictor of Hepatic Steatosis in Adolescents Independently of Obesity. (28th May 2017) - Maldonado-Hernández, Jorge; Saldaña-Dávila, Gabriela E.; Piña-Aguero, Mónica I.; Núñez-García, Benjamín A.; López-Alarcón, Mardia G.
Abstract : Objective . To assess the association between plasma ceramides and hepatic steatosis (HS) in adolescents, independently of obesity. Materials and Methods . Ninety-four adolescents from two previous studies conducted and published by our crew were included. Study subjects were stratified in three groups: normal weight (n = 18 ), obesity (n = 34 ), and obesity + HS (n = 42 ). The presence of HS was defined when ALT/AST ratio was <1. Ceramides subspecies (C14:0, C16:0, C18:0, C24:0, and C24:1) were determined by LC/MS. Results . All ceramides correlated directly with ALT levels and inversely with ALT/AST ratio; the strongest correlation was observed among C14:0 ceramide (r = 0.41 and r = - 0.54, resp.; P < 0.001 ). Furthermore, significant correlations were observed between cholesterol and all ceramides except for C24:1 ceramide. Interestingly ceramides C14:0, C18:0, and C24:1 correlated directly with both fasting insulin and HOMA-IR index. For assessing HS, a cut-off point of 10.3 nmol/L for C14:0 ceramide reported a sensitivity of 92.7% and a specificity of 73.5% when normal weight and obesity groups (n = 52 ) were compared against obesity + HS group (n = 42 ). Positive and negative predictive values were 77.5% and 90.2%, respectively. Conclusions . Plasma ceramides are closely associated with hepatic steatosis in adolescents. C14:0 ceramide could be a novel biomarker of HS independently of obesity.